PENANAMAN NASIONALISME MELALUI EKSTRAKURIKULER SENI TARI TRADISIONAL DI SEKOLAH DASAR - ROFIAH DWI LESTIANA; ENDANG SRI MARUTI; MELIK BUDIARTI (Universitas Trilogi, 2022)
This study aims to portray the cultivation of nationalism through extracurricular traditional dance and nationalism character embedded in students who take extracurricular traditional dance in SDN Patihan City of Madiun. The sample of the study was extracurricular teachers of traditional dance and five students who took extracurricular activities in a traditional dance at Patihan Elementary School in Madiun City. The study was conducted through observation, interviews, and documentation. Data collection instruments used observation sheets, interview guides, and extracurricular values documents of students' traditional dance. Data analysis was carried out through three stages, namely data reduction, data presentation, and concluding. The results showed1) the cultivation of nationalism through extracurricular traditional dance in SDN Patihan City of Madiun was carried out in three domains, namely cognitive, affective, and psychomotor; 2) the character of nationalism embedded in students, namely appreciation of the national culture itself, maintaining the nation's cultural richness, love of the motherland, discipline, respecting cultural diversity, ethnicity, and religion, and working together. The six characters are manifested both incognitive, affective, and psychomotor.